Molecular bridging of mitotic RanGTP and Aurora B kinase in the maintenance of kinetochore-microtubule attachments - Lee, Yoke Peng (2012)
The multi-faceted RanGTPase has been implicated to be critically involved in nucleocytoplasmic transportation and cell cycle progression. However, the role of mitotic RanGTP in kinetochore-microtubule attachments at metaphase has yet to be described. Here, we report a molecular link between the mitotic RanGTP and Aurora B kinase in maintaining stable kinetochore-microtubule attachments after proper chromosome congression. In vivo FRET imaging revealed that real-time decay in RanGTP levels at metaphase is coupled with a progressive displacement of pre-aligned chromosomes from the cell equator. An enrichment of mitotic RanGTP is necessary for recruitment of Mst1 to restrict Aurora B kinase’s influence in promoting reorientation of kinetochore-microtubule attachments at the kinetochores. By ensuring the precision of metaphase chromosome alignment prior to chromosome segregation, this additional role of the RanGTP underscores its significance in protecting genomic integrity and preserving the fidelity of mitotic progression.